Pemberian Materi Ilmu Tajwid Dalam Proses Belajar Membaca Al-Qur’an Pada Anak Usia 14-20 Tahun Di Asrama Miftahul Huda Sukaraja - Suhartono, Suhartono; Romdloni, Romdloni; Marlina, Marlina; Ania, Helda Nur (Jurnal Indonesia Mengabdi, 2022)
This activity is a form of solution related to problems that arise in children who are not yet fluent and fluent in reading the Qur'an. And at the same time in order to help caregivers and Miftahul Huda Dormitory Managers in dealing with children who have not mastered the material of tajwid when reading the Qur'an. The methods used in this activity are; (1) Lecture method (2) Sorogan method. while the planning of this activity includes, the preparation stage, the program implementation stage, the evaluation stage The results obtained are that children/students aged 14 – 20 years who take part in this activity, by obtaining tajwid science material, have increased their ability to read the Qur'an more fluently and fluently in accordance with the rules of tajwid science. Of the 9 children/students aged 14-20 years who took part in this activity, there were 7 children/students who were fluent and fluent in reading the Qur'an in accordance with the rules of tajwid 77.7%, while there were 2 students who were not fluent and fluent. in reading the Qur'an 22.3%